A two-photon fluorescent probe for lysosomal zinc ions. Issue 1 (27th October 2015) - Lee, Hyo-Jun; Cho, Chang-Woo; Seo, Hyewon; Singha, Subhankar; Jun, Yong Woong; Lee, Kyung-Ha; Jung, Youngseob; Kim, Kyong-Tai; Park, Seongjun; Bae, Sung Chul; Ahn, Kyo Han
Abstract : A fluorescent probe that selectively detects Zn(ii ) ions in lysosomes has been developed and applied to the two-photon imaging of Zn(ii ) ions in cells and tissues. Abstract : The selective detection of zinc ions in lysosomes over that in cytosol is achieved with a fluorescent probe, which enabled the fluorescence imaging of endogenous zinc ions in lysosomes of NIH 3T3 cells as well as mouse hippocampal tissues by two-photon microscopy under excitation at 900 nm.